Are public state libraries efficient? An empirical assessment using network Data Envelopment Analysis. (December 2018) - Guccio, Calogero; Mignosa, Anna; Rizzo, Ilde
Abstract: In Italy, public state libraries are multi-product organizations preserving ancient books of great historical relevance for future generations, and providing divisible services to the public. Hence, they may undertake different activities for conservation and use, which together constitute a network. This paper shows the importance of considering multi-process interactions in evaluating the overall performance of public state libraries and focuses on library operations and their sub-processes. It uses a network two-stage Data Envelopment Analysis (DEA) approach to examine the relationship between the libraries' basic inputs, intermediate outputs and final outputs. The main result is that Italian public state libraries generally perform better in the first stage of conservation, but score poorly in the second stage of use. Some policy advice to improve the decision-making process follow Highlights: Public state libraries undertake different activities, which together create a network. Comparison of network two-stage and standard DEA to assess the performance. Standard DEA tend to overstate efficiency of libraries for conservation and use. Efficiency in each stage reveals the presence of sub-technologies absent in standard DEA. Most of the inefficiencies are produced in the second stage of the production process.